Description of Pain Levels in Gout Arthritis Patients in the Kertosari Work Area for the Period February – April 2025 - Firmanti, Tria Anisa; Nadya Cahyaning Pratiwi; Fajri Andi Rahmawan; Sholihin; Supriyanto (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Gouty arthritis is a disease of the musculoskeletal system that attacks the joints with the main problem of pain due to the accumulation of monosodium urate crystals that cause an inflammatory response. The purpose of this study was to determine the description of the level of pain in gouty arthritis patients in the Puskesmas Kertosari Working Area for the period February-April 2025. This research method used a descriptive case series survey research design with a purposive sampling technique on 25 respondents according to the inclusion criteria. The instrument used was the Verbal Rating Scale (VRS). The results of this study showed that half of them experienced severe pain 50% with the characteristics of respondents almost half aged 61 - 68 years (37.5%), and most were male (58.3%). The results of this study can be used as a guideline in pain management in gouty arthritis and become a reference for further research..